З історії відділу етнології російського народу Інституту Етнології та Антропології РАН - Поліщук, Н. (Народна творчість та етнографія, 2005)
The article describes the history of the Russian People Department, which has been established at the Institute of Ethnolography in 1943 (since 1986 “The Department of Ethnology of the Russian People”). During the initial years of the department's existence the focus of research was the observation in daily life of the so called 'pre-capitalist survivals'. The turn to the study of contemporary issues in the life of the people happened at the end of the 1940s/ In 1960-80s socio-normative and spiritual culture of Russians, and the transmissions of tradition were in the focus of attention. During the 60 years of the Department's existence its scholars have published tens of monographs and thematic article collections and hundreds of articles.